(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
If a medical institution has a medical information system that allows you to maintain a Med card, data from examinations, studies, and immunizations will be exported to the existing database. Thus, maintaining a Med card will allow you to analyze population data according to all the criteria of a medical card. Consistent filling of data by all institutions involved in assessing a person’s health and treatment will allow doctors to have a complete basis for analysis and decision-making, and will eliminate the shortcomings associated with the loss of medical data, information about vaccinations, past diseases, etc.